2022
DOI: 10.1155/2022/2593844
|View full text |Cite|
|
Sign up to set email alerts
|

Application Value of MRI Combined with MSCT in Diagnosis and Staging of Colon Carcinoma

Abstract: Objective. To clarify the application value of magnetic resonance imaging (MRI) combined with multislice spiral computed tomography (MSCT) in the diagnosis and staging of colon carcinoma (CC). Methods. A total of 103 patients with histopathologically diagnosed CC were enrolled. Patient clinical and imaging data were collected, and MRI and MSCT images were analyzed to assess the accuracy of MRI, MSCT, and their combination in diagnosing tumor (T) staging of CC. Results. Among the 103 cases of histopathologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…(51)(52)(53)(54) Due to their ability to visualize the intestinal wall, lumen, and their surroundings, MRIs can be promising for the assessment of the small bowel, an organ otherwise very challenging for most imaging methods, and has been utilized, e.g., in the evaluation of patients with Crohn's disease. (55)(56)(57) While MRIs of the colon are routinely used in the staging and monitoring of colon cancer, (58)(59)(60) recent studies have explored their use in the assessment of colonic motility. (61,62) Classically, different MRI sequences have been used in the diagnosis of GI diseases:…”
Section: Practical Applicationsmentioning
confidence: 99%